From The Viewpoints of Afghan University Lecturers, Using the Communicative Language Teaching Method to Teach and Learn English Language - Wahidullah Alokozay; Noorullah Shadab; Emal Shamar (Randwick International of Education and Linguistics Science Journal, 2023)
Investigating how English as a Foreign Language (EFL) instructors at Afghan public universities felt about the application of Communicative Language Teaching (CLT) was the aim of this study. The study used a quantitative research design that included a survey questionnaire. The survey questionnaire was completed by fifty Afghan EFL instructors, and the results were evaluated using descriptive statistics (mean, standard deviation, and frequency). Overall, the findings demonstrated that CLT is seen well by Afghan EFL instructors. The most favourable opinions regarding the role of students in CLT were displayed, suggesting that students firmly think that learners have a crucial role in putting CLT into practice. The role of quality/quantity of error-correction had the lowest mean. The overall findings showed that the Afghan EFL lecturers have positive perceptions about. Future research should be done, according to this study, to learn more about the opinions of Afghan EFL lecturers at both public and private universities. Teachers, students, and policymakers should all take note of the current findings. Curriculum revisions are implemented by policymakers to align with the nation's adoption of CLT.